Cell death in ovarioles causes permanent sterility in Frieseomelitta varia worker bees - Boleli, Isabel Cristina [UNESP]; Paulino-Simões, Zilá Luz; Bitondi, Márcia Maria Gentile (Wiley, 1999)
Frieseomelitta varia worker bees do not lay eggs even when living in queenless colonies, a condition that favors ovary development and oviposition in the majority of highly social bees. The permanent sterility of these worker bees was initially attributed to a failure in ovary morphogenesis and differentiation. Using transmission electron microscopy we found that at the beginning of the pupal phase the ovaries of F. varia workers are formed by four ovarioles, each of them composed of 1) a terminal filament at the apex of the ovarioles, containing juxtaposed and irregularly shaped cells, 2) a germarium with clusters of cystocytes and prefollicular cells showing long cytoplasmic projections that envelop the cystocyte clusters, 3) fusiform interfollicular and basal stalk precursor cells, and 4) globular, irregularly contoured basal cells with large nuclei. However, during the pupal phase an accentuated and progressive process of cell death takes place in the ovarioles. The dying cells are characterized by large membrane bodies, electron-dense apoptotic bodies, vacuoles, vesiculation, secondary lysosomes, enlarged rough endoplasmic reticulum cisternae, swollen mitochondria, pycnotic nuclei, masses of chromatin adjacent to the convoluted nuclear envelope, and nucleoli showing signs of fragmentation. Cell death continues in ovarioles even after the emergence of the workers. Once they become nurse bees, the ovaries have become transformed into a cell mass in which structurally organized ovarioles can no longer be identified. In F. varia workers, ovariole cell death most certainly is part of the program of caste differentiation.
Keywords: Cell death; Ovaries; Stingless bees; animal; bee; cell death; cytology; electron microscopy; female; growth, development and aging; infertility; insect; oocyte; ovary; physiology; ultrastructure; Animals; Bees; Cell Death; Female; Infertility; Microscopy, Electron; Ovary; Ovum; Pupa